Present status and application prospects of green chitin nanowhiskers: A comprehensive review - Zhang, Juanni; Farhan, Mohd Said; Nur Fathin Shamirah, Daud; Jing, Zhanxin (Elsevier Ltd, 2024)
Petrochemical resources are non-renewable, which has impeded the development of synthetic polymers. The poor degradability of synthetic polymers poses substantial environmental pressure. Additionally, the high cost of synthetic biopolymers with excellent degradation performance limits their widespread application. Thus, it is crucial to seek green, sustainable, low-cost polymers as alternatives to petrochemical-based synthetic polymers and synthetic biopolymers. Chitin is a natural and renewable biopolymer discovered in crustacean shells, insect exoskeletons, and fungal cell walls. Chitin chains consist of crystalline and amorphous regions. Note that various treatments can be employed to remove the amorphous region, enhancing the crystallinity of chitin. Chitin nanowhiskers are a high crystallinity nanoscale chitin product with a high aspect ratio, a large surface area, adjustable surface morphology, and biocompatibility. They discover widespread applications in biomedicine, environmental treatment, food packaging, and biomaterials. Various methods can be utilized for preparing chitin nanowhiskers, including chemical, ionic liquids, deacetylation, and mechanical methods. However, developing an environmentally friendly preparation process remains a big challenge for expanding their applications in different materials and large-scale production. This article comprehensively analyzes chitin nanowhiskers' preparation strategies and their drawbacks. It also highlights the extensive application in different materials and various fields, besides the potential for commercial application.